Analisis Pengaruh Faktor Eksternal: Tingkat Inflasi, Suku Bunga BI, dan Pertumbuhan Ekonomi (GDP) terhadap Risiko Kredit Pada Bank Syariah (NPF) - sucik lestari; Khoiriyah, Rahmawati (Journal of Economics and Business Research (JUEBIR), 2024)
This research aims to analyze the influence of inflation, BI interest rates, and economic growth (GDP) on NPF (Non-performing Financing). This study was conducted on Sharia Banks registered with Sharia Commercial Banks (BUS) in 2018-2022. The data used is secondary data from the annual reports of Sharia Banks. The sampling technique was purposive sampling, obtaining a research sample of 55 data. The research method used is a quantitative research method using data analysis techniques, namely panel data regression analysis, while data processing uses the Eviews 10 program. The research results show that the BI interest rate has a positive effect on NPF (Non-performing financing). Meanwhile, inflation and economic growth (GDP) has a negative effect on NPF (Non-performing financing).